INCREASING TAXPAYER COMPLIANCE THROUGH THE QUALITY OF FISKUS SERVICES WITH RISK PREFERENCE AS A MODERATING VARIABLES - yuwita ariessa pravasanti; Desy Nur Pratiwi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
This study aims to determine tax authorities' effect on taxpayer compliance with risk preference as a moderating variable. This type of research is causality research with a quantitative approach. The data used are primary. Namely, the population questionnaire used for this study is all taxpayers KPP Pratama Surakarta. The sample in this study was determined using the purposive sampling method of 50 respondents. The data collection method in this study used a questionnaire. They are testing the results of the questionnaire used validity analysis and reliability analysis. The results show that there is a significant effect of tax authorities on risk preferences. There is an effect of tax services on taxpayer compliance, and risk preference can moderate tax authorities' effect on taxpayer compliance.